The Phenomenology of Maritime Piracy Experiences of Filipino Seafarers - Simon, Evee Kae D (Archīum Ateneo, 2015)
The study aimed to understand how Filipino seafarers make sense of their maritime piracy experiences. A phenomenological analysis was conducted on data gathered from semi-structured interviews with three Filipino seafarers who have had firsthand experiences of maritime piracy. Analysis results revealed nine salient themes under two categories. The first category included themes related to the piracy experience: fear and helplessness, holding onto protocol, prayer as an automatic coping response, and the importance of family. The second category was comprised of themes related to the seafarer schema: seafarer understanding of piracy, the seafarer’s fortitude (“buo ang loob”), the plight of seafarers, seafaring as a passion, and piracy as part of the job. Implications for trauma research and interventions for piracy-affected seafarers are discussed.